Blow up and Growth of Solutions for a Kirchhoff-Type Plate Equation With Degenerate Damping - Ekinci, Fatma; Pişkin, Erhan (Sarajevo Journal of Mathematics, 2024)
We investigate a Kirchhoff-type plate equation with a degenerate damping term. We prove blow up and exponential growth of the solution under some sufﬁcient conditons on the initial data.